ANALISA PEMINJAMAN BUKU PERPUSTAKAAN DENGAN MENGGUNAKAN SISTEM RFID PADA PERGURUAN TINGGI RAHARJA - Untung Rahardja; Yessi Frecilia; Nurul Komaeni (CCIT Journal, 2015)
Advantages of a technology requires the media to support the process of understanding. Methods that can be used to store or receive data remotely by usinga tool called RFID tags or transponders. One methodthat can be used by officers of the library is still in a process of semi-computer to the process of borrowingbooks in the library. Though the process already usethe technology is there, but officers still commit twicethe work. The constraints of the process due to still use big book for data pribadi will borrow books raharja, who later data will be transferred to a computer by using micsrosoft excel. To overcome the various problems as described above, can be done by usingadditional technology to support the activities of the loaning library using RFID. Then needed a quick and efficient process to resolve problems that occur above.The current process of borrowing and pemindahan data are still semi-computer.